Frame-based Stereotactic Biopsy: Description and Association of Anatomical, Radiologic, and Surgical Variables with Diagnostic Yield in a Series of 407 Cases - Lara-Almunia, Monica; Hernandez-Vicente, Javier (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Study Aims Stereotactic biopsy is a versatile, minimally invasive technique to obtain tissue safely from intracranial lesions for their histologic diagnosis and therapeutic management. Our objective was to determine the anatomical, radiologic, and technical factors that can affect the diagnostic yield of this technique. We suggest recommendations to improve its use in clinical practice.Methods This retrospective study evaluated 407 patients who underwent stereotactic biopsies in the past 34 years. The surgical methodology changed through time, distinguished by three distinct periods. Different stereotactic frames (Todd-Wells, CRW, Leksell), neuroimaging tests, and planning programs were used. Using SPSS software v.23, we analyzed a total of 50 variables for each case.Results The series included 265 men (65.1%) and 142 women (34.9%) (average age 53.8 years). The diagnostic yield was 90.4%, morbidity was 5.65% (n = 17), and mortality was 0.98% (n = 4). Intraoperative biopsy improved accuracy (p = 0.024). Biopsies of deep lesions (p = 0.043), without contrast enhancement (p = 0.004), edema (p = 0.036), extensive necrosis (p = 0.028), or a large cystic component (p = 0.023) resulted in a worse diagnostic yield. Neurosurgeons inexperienced in stereotactic techniques obtained more nondiagnostic biopsies (p = 0.043). Experience was the clearest predictive factor of diagnostic yield (odds ratio: 4.049).Conclusions Increased experience in stereotactic techniques, use of the most suitable magnetic resonance imaging sequences during biopsy planning, and intraoperative evaluation of the sample before finalizing the collection are recommended features and ways to improve the diagnostic yield of this technique.
Keywords: stereotactic biopsy; diagnostic yield; stereotactic techniques; brain tumor